Dysregulated expression of IDO may cause unexplained recurrent spontaneous abortion through suppression of trophoblast cell proliferation and migration - Zong, Shanshan (Sci Rep, 2016)
In pregnancy, trophoblast proliferation, migration and invasion are important for the establishment and maintenance of a successful pregnancy. Impaired trophoblast function has been implicated in recurrent spontaneous abortion (RSA), a major complication of pregnancy, but the underlying mechanisms remain unclear. Indoleamine 2,3-dioxygenase (IDO), an enzyme that catabolizes tryptophan along the kynurenine pathway, is highly expressed in the placenta and serum during pregnancy. Here, we identified a novel function of IDO in regulating trophoblast cell proliferation and migration. We showed that IDO expression and activity were decreased in unexplained recurrent spontaneous abortion (URSA) compared to normal pregnancy. Furthermore, blocking IDO in human trophoblast cells led to reduced proliferation and migration, along with decreased STAT3 phosphorylation and MMP9 expression. Increased STAT3 phosphorylation reversed the IDO knockdown-suppressed trophoblast cell proliferation and migration. In addition, the overexpression of IDO promoted cell proliferation and migration, which could be abolished by the STAT3 signaling inhibitor (AG490). Finally, we observed similar reductions of STAT3 phosphorylation and MMP9 expression in URSA patients. These results indicate that the level of IDO expression may be associated with pregnancy-related complications, such as URSA, by affecting trophoblast cell proliferation and migration via the STAT3 signaling pathway.